Self‐affirmation reduces the socioeconomic attainment gap in schools in England. (4th June 2019) - Hadden, Ian Robert; Easterbrook, Matthew John; Nieuwenhuis, Marlon; Fox, Kerry Jane; Dolan, Paul
Abstract : Background: Studies in the United States show that school students from some ethnic backgrounds are susceptible to stereotype threat, that this undermines their academic performance, and that a series of virtually zero‐cost self‐affirmation writing exercises can reduce these adverse effects. In England, however, socioeconomic status (SES) is a much stronger predictor of academic success than is ethnic background. Aims: This study investigates whether self‐affirmation writing exercises can help close the SES attainment gap in England by increasing the academic performance of low‐SES (but not higher‐SES) school students. Sample: Our sample consisted of students aged 11–14 in a secondary school in southern England ( N  = 562); of these, 128 were eligible for free school meals, a proxy for low SES. Methods: Students completed three short writing exercises throughout one academic year: those randomly assigned to an affirmed condition wrote about values that were important to them, and those assigned to a control condition wrote about a neutral topic. Results: On average, the low‐SES students had lower academic performance and reported experiencing more stereotype threat than their higher‐SES peers. The self‐affirmation raised the academic performance of the low‐SES students by 0.38 standard deviations but did not significantly affect the performance of the higher‐SES students, thus reducing the SES performance gap by 62%. The self‐affirmation also reduced the level of stress reported by the low‐SES students. Conclusions: The benefits of this virtually zero‐cost intervention compare favourably with those of other interventions targeting the SES academic attainment gap.